2017
DOI: 10.1080/13607863.2017.1376313
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity in older adults’ theory of mind performance: the impact of motivation

Abstract: These results indicate that motivation can enhance older adults' performance in ToM tasks, however, this beneficial effect cannot be generalized across ToM tasks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 49 publications
2
12
0
Order By: Relevance
“…Hence, the authors hypothesized that the manipulation of perceived closeness may increase emotional meaningfulness and potential motivation in accomplishing a task, thus leading to better performance. In line with their expectations, the authors found that perceived closeness enhanced older Chinese participants’ performance on both ER and ToM tasks [24,25].…”
Section: Introductionsupporting
confidence: 61%
See 4 more Smart Citations
“…Hence, the authors hypothesized that the manipulation of perceived closeness may increase emotional meaningfulness and potential motivation in accomplishing a task, thus leading to better performance. In line with their expectations, the authors found that perceived closeness enhanced older Chinese participants’ performance on both ER and ToM tasks [24,25].…”
Section: Introductionsupporting
confidence: 61%
“…On the one hand, accountability should increase motivation and performance, yet Stanley and Isaacowitz [26] found that it did not significantly improve older adults’ emotion recognition performance. On the other hand, Zhang et al [24,25] and Stanley and Isaacowitz [26] manipulated familiarity in markedly different ways, and found that it did improve older adults’ social-cognition.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations